PENGEMBANGAN TUJUAN PEMBELAJARAN PAI DI POLITEKNIK BERBASIS MAKNA JIHAD PADA AYAT-AYAT MAKKIYYAH - Suhendar, Waway Qodratulloh (Universitas Pendidikan Indonesia, 2021)
Abstract. This article examines the meaning of jihad in Makkiyyah verses in developing Islamic Religious Education (IRE) learning at the Polytechnic of Bandung. Practically, the results of this study aim to obtain the right formula in developing the learning objectives of IRE courses at the Polytechnic. This study uses a qualitative approach with a descriptive-analytical method, and analyzes it with a deduction and induction method. The results of the study show that the meaning of jihad in the Makkiyyah verses is related to sincerity with all abilities to be firm in believing in Allah and being able to actualize it according to the existing situation and conditions. The implication of the meaning of jihad in the Makkiyyah verses in developing Islamic Religious Education (IRE) learning objectives at the Polytechnic is to become the basis for developing the personality of students to become professionals who believe and are able to empower all their potential.Abstrak. Artikel ini mengkaji secara mendalam mengenai makna jihad pada ayat-ayat Makkiyyah dalam pengembangan pembelajaran Pendidikan Agama Islam (PAI) di Politeknik Bandung. Secara praktis, hasil kajian ini bertujuan agar didapatkan formula yang tepat dalam pengembangan tujuan pembelajaran mata kuliah PAI di Politeknik. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitis, dan menganalisisnya dengan metode deduksi dan induksi. Hasil penelitian menunjukan makna jihad dalam ayat-ayat Makkiyyah berkaitan dengan kesungguhan atas segenap kemampuan untuk teguh dalam keyakinan kepada Allah dan mampu mengaktualisasikan sesuai dengan situasi dan kondisi yang ada. Implikasi makna jihad pada ayat-ayat Makkiyyah dalam pengembangan tujuan pembelajaran PAI di Politeknik adalah menjadi landasan pengembangan kepribadian mahasiswa agar menjadi profesional yang beriman dan mampu memberdayakan seluruh potensinya.